2015
DOI: 10.1080/14703297.2014.1003954
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the assessment experience: improving student perceptions, engagement and understanding using online video feedback

Abstract: Individualised video screencasts with accompanying narration were used to provide assessment feedback to a large number (n = 299) of first-year Bachelor of Education students at Edith Cowan University in Western Australia. An anonymous online survey revealed that nearly three times as many respondents (61%) preferred video feedback to written feedback (21%). The results reflect a clear preference for video feedback among the research participants. Participants commented that video feedback was clearer and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 17 publications
4
67
0
1
Order By: Relevance
“…The results presented in this section partially support H1, and reaffirm previous findings that digital recordings are an effective mode for detailed and personalised feedback comments (Knauf, ; Orlando, ; West & Turner, ). However, the hypothesis that digitally recorded comments would be perceived as more usable than other modes was not supported.…”
Section: Resultssupporting
confidence: 88%
“…The results presented in this section partially support H1, and reaffirm previous findings that digital recordings are an effective mode for detailed and personalised feedback comments (Knauf, ; Orlando, ; West & Turner, ). However, the hypothesis that digitally recorded comments would be perceived as more usable than other modes was not supported.…”
Section: Resultssupporting
confidence: 88%
“…The opposite was true for the mean scores of other two constructs, performance and self-efficacy. Having high performance test score with text only feedback, which contradicts the studies carried out by Hung (2016) and West and Turner (2016), can be explained with the useful, satisfactory and explanatory written feedback (Gibbs & DunbarGoddet, 2007;Lees & Carpenter, 2012;Lu & Law, 2012;Nisbet, 2004;Ruegg, 2014;Xiao & Lucking, 2008;Yu & Wu, 2013). Some written feedback was even stated step by step: "Your assignment; -include only one paragraph -text must be left aligned -space after paragraph must be 10nk -Line space must be 12nk -Subscript must be used in the first word of the sentence and applied on the fourth and fifth characters."…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a web-based tool developed to conduct self and peer-assessment flexibly was found efficient in improving the quality of students' work after they received feedback (Sung, Chang, Chiou & Hou, 2005). West and Turner (2016) stated that online video feedback increased the quality and quantity of feedback received and was preferred more than the other forms of feedback among the participants. In another study, Hung (2016) investigated the influence of multimodal video and text-based feedback on learner engagement respectively and found that students favored the video feedback.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…The study also showed that the students not only appreciate but actually need endlessly feedback (West & Turner, 2015) in order to develop as students, learners, and members of an academic community (Winstone, Nash, Rowntree, & Parker, 2016). In addition to the support of the university community as a whole, all this is greatly based on positive attitudes toward studies and tasks, study community and peers.…”
Section: Journal Of Studies In Educationmentioning
confidence: 99%